2013
DOI: 10.7822/egt238
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarinin Eği̇ti̇m Fakültesi̇nde

Abstract: Özet: Eğitim kurumlarındaki eğitim-öğretim faaliyetlerinin gözden geçirilmesi ve yeniden yapılanması sürecinde öğrencilerin memnuniyet düzeyleri ve görüşleri önem taşımaktadır. Bu çalışmada eğitim fakültesinde öğrenim gören öğretmen adaylarının eğitim hizmetlerinden duydukları memnuniyet düzeyleri çeşitli değişkenler açısından belirlenmeye çalışılmıştır. Araştırma 2012-2013 öğretim yılında Ondokuz Mayıs Üniversitesi Eğitim Fakültesinde gerçekleştirilmiştir. Araştırmada öğretmen adaylarının memnuniyet düzeyleri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…At the same time, education becomes more fun and enjoyable thanks to computers (Huang, 2003). Even though computers initially entered the education system only as a tool to help teachers, today, thanks to various software programs developed, they enable students to learn the subject at their own pace (Tor & Erden, 2004), reinforce the subject learned through exercises, do practices on their own (Yiğit et al, 2007) and even acquire knowledge by making discoveries (Özçakır Sümen, 2013). The use of technology in especially teaching Mathematics lessons, which students see as a difficult school subject (Azid, Hasan, Nazarudin, & Md-Ali, 2020;Bwalya, 2019;Cengiz, 2017;Fabian, Topping & Barron, 2018) has begun to increase rapidly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, education becomes more fun and enjoyable thanks to computers (Huang, 2003). Even though computers initially entered the education system only as a tool to help teachers, today, thanks to various software programs developed, they enable students to learn the subject at their own pace (Tor & Erden, 2004), reinforce the subject learned through exercises, do practices on their own (Yiğit et al, 2007) and even acquire knowledge by making discoveries (Özçakır Sümen, 2013). The use of technology in especially teaching Mathematics lessons, which students see as a difficult school subject (Azid, Hasan, Nazarudin, & Md-Ali, 2020;Bwalya, 2019;Cengiz, 2017;Fabian, Topping & Barron, 2018) has begun to increase rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…In many of the studies present in the literature, it can be noticed that GeoGebra provides effective learning in Mathematics teaching (Barçın, 2019;Boo & Leong, 2016;Bwalya, 2019;Doğan & İçel, 2011;Genç, 2010;Hussin, Yusoff, Mustaffa & Mokmin, 2018;Özçakır Sümen, 2013;Ünlütürk Akçakın, 2016;Zengin, 2019). However, it is observed that these studies are generally carried out in educational institutions at the secondary school level and above.…”
Section: Introductionmentioning
confidence: 99%